COMPARATIVE STUDY OF RHOMBOID (LIMBERG) FLAP CLOSURE WITH WIDE OPEN EXCISION IN MANAGEMENT OF PILONIDAL SINUS - VISHAL SOLANKI; SUMAN PARIHAR; MOHIT KUMAR BADGURJAR; NEHA BAPORIKAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective- There are may options for the treatment of pilonidal sinus with different pros and cons . The current study intends to compare two commonly practiced surgical treatments -Rhomboid excision (Limberg flap repair) against wide-open excision with healing by secondary intention. In this study, we have compared post operative complications and recurrence rates after Limberg Flap and wide excision. Materials and Methods: Our study is a prospective study including 56 patients who were admitted for pilonidal sinus and operated by Limberg flap reconstruction surgery and Wide Local Excision at a tertiary centre. Results: The patients included males and females in a ratio of 4.6:1 .The mean presenting age of the patients was 32.84 years .Most common presenting complaint was discharge from affected site and local pain. Operating time was observed to be significantly more for Limberg Flap as compared to for wide local excision. Hospital stay was noted to be longer for wide local excision than Limberg Flap with a p-value <0.0001. Post op complications like bleeding, wound dehiscence as well as recurrence was noted more in Wide Local excision. Pain free sitting days were less in Limberg Flap and return to work was much earlier as compared to Wide Local Excision. Conclusions: Limberg flap reconstruction surgery is the most preferred method of treatment for pilonidal sinus because of its less discomfort, low infection and low recurrence rates, better aesthetic results after surgery and short duration of hospital stay and return to work.